Answer:
f(-3) = -1
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
- Functions
- Function Notation
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
f(x) = -1x - 4
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em> [Function f(x)]: f(-3) = -1(-3) - 4
- Multiply: f(-3) = 3 - 4
- Subtract: f(-3) = -1
Answer:
It D
Step-by-step explanation:
k
Answer:
124 tiles
Step-by-step explanation:
2(20+40)
2(60)
120+4=124
Answer:
10
Step-by-step explanation:
Answer:
60 square units
Step-by-step explanation: